2010
DOI: 10.1007/s10549-010-1015-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis reveals a different transcriptomic landscape in female and male breast cancer

Abstract: Results -Almost 1000 genes were found differentially expressed (FDR<1%) between female and male patients and biological interpretation highlighted a gender associated modulation of key biological processes ranging from energy metabolism to regulation of translation and matrix remodeling as well as immune system recruitment. Moreover, an analysis of genes correlated to steroid receptors and ERBB2 suggested a prominent role for the androgen receptor in MBC with a minor relevance for progesterone receptor and ERB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 55 publications
3
66
0
Order By: Relevance
“…Callari et al [16] compared gene expression profiles of 37 ER-positive MBC specimens to those of 53 ER-positive FBC specimens. Almost 1,000 genes were found to be differentially expressed in female and male patients, and biological interpretation highlighted a gender-associated modulation of key biological processes ranging from energy metabolism to regulation of translation and matrix remodeling as well as immune system recruitment [16]. Johansson et al [17] described two unique subgroups of MBC with differences in tumor biological features and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Callari et al [16] compared gene expression profiles of 37 ER-positive MBC specimens to those of 53 ER-positive FBC specimens. Almost 1,000 genes were found to be differentially expressed in female and male patients, and biological interpretation highlighted a gender-associated modulation of key biological processes ranging from energy metabolism to regulation of translation and matrix remodeling as well as immune system recruitment [16]. Johansson et al [17] described two unique subgroups of MBC with differences in tumor biological features and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…4 Other studies have also indicated a different role of steroid receptors in male breast cancer, suggesting a reduced functionality of ER. 30,31 Consequently, the ER stimulating effect of cyclin D1 may be limited in male breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Even though array data were exclusively interrogated, to our knowledge, for seven gene expression modules and a signature registering the activity of AR was not scrutinized, this study provided further ground to the heterogeneous nature of MBC. An independent gene expression profiling study carried to retrieve differences between MBC and FBC yielded approximately 1.000 differentially expressed genes [33]. Biological interpretation of this gene set revealed that a significant higher number of AR-related genes were up-regulated in MBC compared with FBC, and overall suggested AR activation.…”
Section: Ar In Mbc: Transcriptome-based Studiesmentioning
confidence: 99%